Neuro-ophthalmologic findings of hypovitaminosis a in beef cattle: a retrospective study - Giulia Cagnotti; Cristina Giordano; Giorgia Di Muro; Sara Ferrini; Chiara Giudice; Giuliano Borriello; Antonio D’Angelo (Veterinary Quarterly)
Vitamin A in cattle is essential due to its antioxidant properties and importance in vision, immune function, reproduction, and cellular differentiation. This study investigates the clinical presentation, diagnosis, and treatment outcomes of hypovitaminosis A in 15 Piedmontese calves, referred to the Veterinary Teaching Hospital in Turin for vision impairment between 2016 and 2024. Neurological and ophthalmological evaluations revealed hypovision or blindness in 87% of cases, with additional epileptic seizures in 13%. Ophthalmological findings included papilledema, optic nerve atrophy, and retinal abnormalities, which were consistent predictors of poor prognosis for vision recovery. Serum vitamin A levels were below the reference range in all cases, confirming a primary dietary deficiency linked to the use of dry, preserved forages.Parenteral administration of vitamin A and dietary supplementation improved clinical outcomes in most cases, with 67% of affected calves achieving complete recovery. Histopathological analysis of one subject revealed ischemic degeneration presumably due to narrowed optic foramina caused by vitamin A deficiency. The findings emphasize the importance of early diagnosis through ocular and neurological assessments to prevent irreversible damage and economic loss in cattle herds. Prompt supplementation can mitigate health and productivity losses, emphasizing its critical role in herd management practices.